MⅡ-polyphosphate-based wax-like material with osteogenesis and blood occlusion - Wei Zhu; Huasi Zhou; Zhanqi Wei; Xisheng Weng; Bin Li; Song Chen; Håkan Engqvist; Sheng Cui; Wei Xia (Bioactive Materials)
There is a constant need for materials that combine hemostasis and osteogenesis in orthopedic surgery. Current hemostatic materials lack biodegradability, osteogenic properties, and hemostatic efficacy. In this study, we developed a wax-like co-doped polyphosphate (CoPPW) by chelating sodium polyphosphate with cationic ions (Ca2+, Mg2+, and Sr2+). Our results demonstrate that CoPPW was malleable and degraded optimally, releasing Mg2+ and Sr2+ ions initially and losing weight over 4 weeks. In vitro, CoPPW promoted better cell proliferation and osteogenic differentiation than beeswax, likely due to ion release. RT-PCR and transcriptome sequencing revealed that CoPPW significantly upregulated osteogenesis-related genes and bone-related protein expression. The activation of the PI3K/AKT signalling pathway confirmed osteogenesis, while the coagulation cascade pathway indicated effective hemostasis. In vivo, CoPPW was more effective in promoting bone regeneration and hemostasis compared to bone wax. Overall, CoPPW exhibits excellent hemostatic and osteogenic effects, making it a promising candidate for bone repair applications.